(untitled) (Journal of Patan Academy of Health Sciences, 2019)
Introductions: Fractures of diaphyseal region of the tibial bone are amongst the most commonly seen extremity injuries in the developing countries. The surgical implant generation network (SIGN) intramedullary (IM) nail was designed for the treatment of long bone fractures in the developing nations. Methods: From March 2008 to December 2018, a total of 104 patients with 104 tibial diaphyseal fractures were treated with SIGN IM nail. The follow-up visits were arranged at 6, 12, 24 weeks and one-year post operatively. During follow-up visits, the signs of fracture union clinically as well as radiologically and the presence of complications any were recorded and analyzed. Results: The mean age of the patients was 32.81 (16 – 65) years, male 74 (71.2%) and female 30 (28.8%). Majority of the patients 70 (67.3%) had fractures after road traffic accidents. The mean time of surgery was 13.58 (1 – 463) days. Six (5.8%) patients had delayed union and no non-union was detected. We had 10 cases (9.6%) of mal-alignment but were on acceptable range. Conclusions: In the developing country like Nepal, the SIGN nail is an effective surgical implant for the management of the tibial diaphyseal fractures with good result of fracture union and low rates of nonunion, mal-alignment and manageable complications.